Analysis of customer satisfaction using surveys with open questions (2014)
In this paper the use of open-ended questionnaires to improve the evaluation of customer satisfaction according to ISO 9001 in small and medium-sized enterprises is analyzed. By obtaining more information in comparison to the closed questions questionnaire some limitations coming from the second one are removed. The open-ended questionnaire is analyzed by applying a semantic study to obtain the root of each word and remove the word that is not relevant for the information needs of the organization. This way the positive or negative trend for each response is identified. This study proofs that the use of open-ended questionnaires facilitates the fulfilment of the ISO 9001 standard. It allows the comparison between the data coming from the Customer Relationship Management System (CRM) and the data obtained through the questionnaire. Furthermore it opens new areas of research based in the use of semantic analysis in quality systems and marketing.